Airway microbiota is associated with the severity of non‐CF bronchiectasis. (14th October 2020) - Li, Liyang; Zhang, Jiaming; Li, Zhuozhe; Zhang, Cuiping; Bi, Jing; Zhou, Jian; Song, Yuanlin; Shao, Changzhou
Abstract: Background: Airway microbiota are associated with several chronic respiratory diseases. However, limited studies examined microbiota in non‐cystic fibrosis (non‐CF) bronchiectasis, especially its relationship with severity and immunology. Objectives: We characterized the microbiota of patients with different severities of bronchiectasis and examined the correlation between microbiota and the immunological indices. Materials and methods: The microbiota of 63 sputum samples from 40 patients with bronchiectasis were analyzed by 16S rRNA gene sequencing. Blood tests and related immunological indices were detected. Results: According to the baseline data of patients with bronchiectasis, we found that more severe bronchiectasis was accompanied by lower prealbumin levels. The 16S rRNA sequencing analyses demonstrated that Pseudomonas‐dominated microbiota produced lower levels of interleukin‐4 (IL‐4) and transforming growth factor‐β (TGF‐β) compared to other‐dominated microbiota. The airway microbiota of patients with mild bronchiectasis clustered apart from those of patients with severe bronchiectasis, which correlated with IL‐4 and other clinical indices. Conclusion: There are differences in the airway microbiota between patients with mild and severe bronchiectasis. The airway microbiota was related to some clinical indices that represent effects on the immune system.